DEVELOPING TEACHING MATERIAL ON NARRATIVE TEXT FOR THE SECOND GRADE STUDENTS AT MTsN 2 MEDAN - Dwita Sundari and Johan (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
The objective of this study was to develop teaching materials on narrative text based on the students’ needs. This study was conducted by using Research and Development (R & D) design. The data was consisted of information who gathered by administering interview to the teacher and distributing questionnaires to the students. The instruments used in this study were questionnaires, interview, and syllabus. The result of this study was a set of developed teaching material. It covered of three units, they were: the story between animal and human, animal, and plant which were included into three texts, they were: Abrahah’s elephant, Neli’s fruit, story between Pleci’s trumpets and its fireworks. Each of the text comprised of three kinds of exercise and in the first page there was an explanation about narrative genre and its social function were provided.